Teacher Performance Reviewed From Work Motivation, Academic Supervision, Teacher Welfare and Competence - Diah Hikmawati; Bambang Mursito; Anita Wijayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the simultaneous and partial effects of work motivation, academic supervision, welfare, and teacher competence on teacher performance at Madrasah Ibtidaiyah in Jebres District, Surakarta City. This research employed a quantitative approach with a survey research design. The population of this study consisted of all teachers working at Madrasah Ibtidaiyah in Jebres District, Surakarta City, totaling 41 teachers. The sampling technique used was a census technique, in which all members of the population were selected as research respondents. Data were collected using questionnaires. The data analysis techniques included multiple linear regression analysis, F-test, t-test, and coefficient of determination. The results indicate that work motivation, academic supervision, teacher welfare, and teacher competence simultaneously have a significant effect on teacher performance at Madrasah Ibtidaiyah in Jebres District, Surakarta City. Furthermore, partial analysis shows that each independent variable has a positive and significant influence on teacher performance. Based on these findings, it is recommended that Madrasah Ibtidaiyah in Jebres District, Surakarta City continuously enhance work motivation, strengthen academic supervision practices, improve teacher welfare, and develop teacher competence in order to improve teacher performance and educational quality. Keywords: Teacher Performance, Work Motivation, Academic Supervision, Teacher Welfare, Teacher Competence